2002
DOI: 10.1590/s0101-31222002000100006
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do vigor de sementes de soja sobre o seu desempenho em campo

Abstract: A pesquisa teve como objetivo estudar o processo de maturação das sementes de calêndula. A partir de 50% dos botões florais em antese, foi feita a marcação das flores, sendo a coleta das sementes realizada em seis épocas: 20, 24, 28, 32, 36 e 40 dias após a antese (DAA). Em cada coleta, as sementes foram separadas pelo tamanho (maior e menor), e classificadas conforme a Tabela de Munsell (Munsell,1977) conforme as colorações observadas: verde, verde claro, creme, marrom claro e marrom escuro. Em seguida, foram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 2 publications
2
6
0
6
Order By: Relevance
“…Within this context, Costa et al (2012) had already demonstrated that the germination test, when performed at 25 °C, and under an osmotic potential of -0.1 MPa simulated with PEG 6000 may be used as a tool to assess vigor of soybean seeds; as it presents a result similar to that obtained through the accelerated aging test. Vanzolini and Carvalho (2002) found that more vigorous seeds produce seedlings with higher length roots; a result that is similar to what was observed in this study. However, herein it was found that under ideal conditions the smaller seeds, identified in the first count of germination test as having lower vigor, produced seedlings with radicles of shorter length (Table 2).…”
Section: Resultssupporting
confidence: 91%
“…Within this context, Costa et al (2012) had already demonstrated that the germination test, when performed at 25 °C, and under an osmotic potential of -0.1 MPa simulated with PEG 6000 may be used as a tool to assess vigor of soybean seeds; as it presents a result similar to that obtained through the accelerated aging test. Vanzolini and Carvalho (2002) found that more vigorous seeds produce seedlings with higher length roots; a result that is similar to what was observed in this study. However, herein it was found that under ideal conditions the smaller seeds, identified in the first count of germination test as having lower vigor, produced seedlings with radicles of shorter length (Table 2).…”
Section: Resultssupporting
confidence: 91%
“…Several species of the Asteraceae show similar behavior to that found in this study for E. mollis, with seed maturation close to 45 DAA (Bezerra et al, 2003;Duarte, Santos, Souza Peixoto, & Santos, 2012;Grzybowski et al, 2016;Guimarães, Oliveira, Mantovani-Alvarenga, & Grossi, 1998;Silveira, Villela, & Tillmann, 2002), with some species showing earlier maturation, such as Adenostemma brasilianum (Pers.) Cass.…”
Section: Discussionsupporting
confidence: 81%
“…On the other hand, the seed traits showed a significant and inverse correlation with NDM (Table 5). Low-vigor seed lots have been shown to prolong the vegetative phase of plants (Vanzolini and Carvalho, 2002), which is intimately related to the reproductive cycle of a genotype.…”
Section: Resultsmentioning
confidence: 99%